The implementation of agent based complaint management system - Md Sultan, Abu Bakar; Zainal Abidin, Khairunnisa; Abdullah @ Selimun, Mohd Taufik (2008)
Complaint management system is a system to enable customers channel the issues about the organization for immediate action. Thus responsive complaint system is essential for the organization to ensure customers satisfaction in managing complaints. This paper introduces the agent-based Complaint Management System (ACM). The objective of the system is autonomously accepted the complaints and forward to the respective responsibility. Initial result, shows the system is able to entertain users complaint with minimal intervention by human. Keyword recognition was proposed as an intelligent element for the system. Future efforts are looking for complete agent- based complaint management system with more intelligent features.